Pesan Dakwah dalam Iklan Ramadan BCA: Analisis Semiotika Charles Sanders Peirce - Sultan Hakim Yusuf; Siroy Kurniawan (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2026)
This study aims to examine how religious messages are represented in BCA’s Ramadan advertisements using Charles Sanders Peirce’s semiotic approach. The method employed is qualitative descriptive research, utilizing observation and documentation techniques, specifically watching and analyzing the dialogue and scenes in the advertisements. The research object is the advertisement video titled “Gigih Raih Kemenangan Ramadan Bersama BCA” (Persevere to Achieve Ramadan Victory with BCA), published on digital platforms. The units of analysis in this study are the audio and visual elements consisting of signs, objects, and interpretants in each scene, which are then linked to the categories of da’wah messages: faith (aqidah), Sharia, and ethics (akhlaq). Data were analyzed across six main scenes containing visual and verbal signs with da’wah undertones. The results indicate that each scene in the advertisement contains symbolic meanings that implicitly represent da’wah values. Specifically, the dominant da’wah messages include moral values such as filial piety toward parents, social compassion, the Sharia of fasting, congregational prayer, and Quranic education within the family. These values emerge through simple yet meaningful visual representations of daily life, thereby shaping a contextual religious understanding. The process of semiosis demonstrates that advertisements not only function as promotional media but also contain a spiritual dimension of meaning that can be interpreted by the audience. The contribution of this research lies in reinforcing the perspective that non-religious mass media has the potential to serve as a vehicle for representing da’wah values, while simultaneously enriching semiotics-based visual communication studies in the context of the dissemination of Islamic values.